On the domestic political-economic sources of American military spending - Thomas R. Cusack (Wissenschaftszentrum Berlin für Sozialforschung (WZB); Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1989)
This paper attempts to demonstrate the significant impact that domestic political-economic factors have in shaping the American defense budget. Evidence is provided which shows that while the military spending burden sustained by the United States is far and away greater than its allies, this may be a function less of free riding on the part of those allies, and more a function of the domestic political-economic needs of the American system. The mutual influence relationship between U.S. military spending and public opinion is then examined and evidence provided which suggests that public support of U.S. political leaders is significantly affected by the arms spending competition between the Soviet Union and the United States during periods when the American public focuses its attention on foreign affairs. Finally, a political business cycle model of American defense spending is examined for the period 1953-1986 and shown to be a useful explanatory device. In particular, it helps illuminate the importance of military spending as policy instrument for economic stabilization and a means of helping secure electoral support from the American public. The analyses in this paper also demonstrate the non-revolutionary character of the Reagan administration defense policies, policies that are very much in keeping with the post-World War II traditions of American administrations. – – Dieser Beitrag versucht, den starken Einfluß innerstaatlicher politisch-ökonomischer Faktoren auf den amerikanischen Verteidigungshaushalt aufzuzeigen. Es wird zwar nachgewiesen, daß die amerikanischen Militärausgaben die der anderen Allierten bei weitem übertreffen, dies konnte jedoch eher an politisch-ökonomischen Zwangen als an dem Trittbrettfahrer-Effekt seitens der Allierten liegen. Die Wechselwirkung zwischen den US-Verteidigungsausgaben und der öffentlichen Meinung wird anschließend untersucht. Die vorliegenden Informationen legen die Vermutung nahe, daß die Unterstiitzung der US-Führung durch die Bevölkerung unter der Bedingung des Rüstungswettbewerbs zwischen den USA und der Sowjet Union dann signifikant variiert, wenn die Aufmerksamkeit der amerikanischen Öffentlichkeit auf die Außenpolitik gerichtet ist. Zum Schluß wird ein politisches Konjunkturzyklusmodell der Verteidigungsausgaben für die Zeit 1953-1986 untersucht, das sich als nützlich für die Erklärung der Rüstungsausgaben erweist. Es wirft weiteres Licht auf die Bedeutung der Rüstungsausgaben als politischem Instrument zur wirtschaftlichen Stabilisierung und als Mittel zur Sicherung der Regierungspopularität. Der Beitrag zeigt außerdem den nicht-revolutionaren Charakter der Reagan-Verteidigungspolitik auf - es war eine Politik, die ganz in der Tradition der Nachkriegsadministrationen stand.
Keywords: 320